Pengembangan Media Pembelajaran Berbasis Video Animasi Kelas IV (Fase B) Pada Materi Metamorfosis - Dongoran, Kristian Federik (Innovative: Journal Of Social Science Research, 2024)
Natural and Social Sciences (IPAS) is an important part of the basic education curriculum. In grade IV, one of the topics taught is metamorphosis. However, conventional learning that is only used to rely on textbooks and teacher lectures can be less varied so that it is less attractive to students. Because of that, in this research, the goal is to develop learning media based on video animation for science learning in class IV (Phase B) on metamorphosis material. This course research utilizes research development (R&D) methods adapted from the Borg and Gall model. Sources of data in this study were interviews, expert validation, and student responses as well as documentation during the use of animated video-based learning media. Data collection techniques used in this study were questionnaires and interviews. The results of this study indicate that the development of animated video-based science learning media has gone through 7 research steps, namely preliminary studies and data collection, planning, initial product development, initial product trials, initial product revisions, field trials, and final product revisions. The feasibility level of the learning media developed is "Very Good" in terms of material and design aspects with an average value of 4.00 and 3.86. As well as the results of the "Very Good" product trial with an average value of 3.79. The development of animated video-based media using the Borg and Gall method can be an effective alternative in learning Science Class IV (Phase B) on metamorphosis material. This media can be a more interesting learning facility in class.